Implementation Of Patient Safety Based On The Availability And Safety Of Use Of Alkesdi In ICU Rooms And Central Surgical Installations Sembiring RSU In 2023 - Nurhidayat, Prawito; Siitepu, Marlen Sadrina; Marbun, Victor Edyward (Program Studi Pendidikan Biologi, 2023)
The population and sample in this study are all medical personnel and medical officers on duty in the ICU Room and Central Surgery Installation as many as 48 people. All variables in this study are statistically related to the Implementation of Patient Safety. The surveillance variable is the most related variable and has a 7,205 times chance of improving the Implementation of Patient Safety at Sembiring Hospital and the majority of Inventory, Decontamination, Surveillance and Recall in the ICU and Central Surgery rooms have been carried out. well executed. The Management of Sembiring Hospital can make changes to the medical device inventory system which was previously carried out manually by using a checklist form to become a barcode system to simplify the inventory process and reduce the error rate in filling out the inventory checklist, so that it will directly result in the implementation of ordering medical equipment and inventory to be more efficient. optimally and need to optimize supervision of the Implementation of Patient Safety by officers of all medical personnel and medical officers by consistently filling out the checklist form for the implementation of inventory, decontamination, surveillance and recall of medical devices so that it can help facilitate the performance of electromedical technicians, especially in carrying out maintenance activity schedules and checklists equipment to be maintained.